Pengaruh Team Work Dan Disiplin Kerja Pada Multi National Company (MNC) Terhadap Kinerja Karyawan - Suhardoyo (Majalah Ekonomi, 2021)
Companies in achieving optimal performance require team work and work discipline from employees to support their achievements. So this study aims to test and prove empirically: the effect of team work directly on employee performance, the effect of work discipline on employee performance directly and team work and discipline together have a direct effect on performance. This study is an explanatory research with a population of 150 respondents, this study was analyzed through Linear Regression Analysis with the help of SPSS 23 software. The results showed a constant value of -0.77 stating that if the independent variables of team work and work discipline did not exist, then employee performance will decrease by -0.77 units. While the team work coefficient value of 0.617 states that the team work variable has a positive and significant impact on employee performance, or in other words, every 1 increase in team work scores will be followed by employee performance of 0.617 units. The work discipline coefficient value of 0.721 states that the work discipline variable has a positive and significant effect on employee productivity, or in other words, every 1 increase in team work score will be followed by an increase in employee productivity of 0.721 units. So that team work and employee work discipline need to be continuously improved so as to improve employee performance at the multi-national company PT. DS Global to maintain the company's survival.